This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There is no reason to do that. Just cancel and take derivative.
oh yeah, you are right, didn't see that.
Log in to reply
Your solution is perfectly fine too; just takes a little longer.
x 2 − 1 = ( x + 1 ) ( x − 1 ) , so divide out a factor x − 1 whenever x = 1 . Now d x d ( x + 1 ) = 1 . The value is undefined at x = 1 , the problem should exclude 1 from the domain.
x − 1 x 2 − 1 = x − 1 ( x − 1 ) ( x + 1 ) = x + 1 . The derivative of this is simply the slope, or 1.
Problem Loading...
Note Loading...
Set Loading...
Solving it using the quotient rule of derivatives we get ( x − 1 ) 2 2 x ( x − 1 ) − x 2 + 1 = ( x − 1 ) 2 ( x − 1 ) 2 = 1